The republic : and, the laws - Cicero, Marcus Tullius (Oxford world's classics (Oxford University Press), 1998)
However one defines Man, the same definition applies to us all. This is sufficient proof that there is no essential difference within mankind.' (Laws l.29-30) Cicero's The Republic is an impassioned plea for responsible governement written just before the civil war that ended the Roman Republic in a dialogue following Plato. Drawing on Greek political theory, the work embodies the mature reflections of a Roman ex-consul on the nature of political organization, on justice in society, and on the qualities needed in a statesman. Its sequel, The Laws, expounds the influential doctrine of Natural.